"Billion Dollar Brain" -elokuvan kuvaukset
content description: Making of the film "The Billion Dollar Brain" in Helsinki February 1967. Michael Caine in the centre, Harry Saltzman to the right.
Keywords: films; English people; cinematography; actors (stage artists); cinema; films; movies; filmmaking; actors; British films; Caine, Michael